2021
DOI: 10.1038/s41467-021-25652-x
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal access to organic nitrogen mediates CO2 fertilization response in a dominant temperate tree

Abstract: Plant–mycorrhizal interactions mediate plant nitrogen (N) limitation and can inform model projections of the duration and strength of the effect of increasing CO2 on plant growth. We present dendrochronological evidence of a positive, but context-dependent fertilization response of Quercus rubra L. to increasing ambient CO2 (iCO2) along a natural soil nutrient gradient in a mature temperate forest. We investigated this heterogeneous response by linking metagenomic measurements of ectomycorrhizal (ECM) fungal N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 105 publications
1
33
0
Order By: Relevance
“…Specifically, investment in ECM symbionts with energetically costly organic N acquisition capacities is beneficial to plant hosts where inorganic N is scarce, favouring ECM taxa with a greater genetic potential to obtain N from SOM using peroxidases and other oxidative enzymes (Baskaran et al, 2017;Defrenne et al, 2019;. These decay traits enable ECM communities in soils with low inorganic N availability to more substantially supplement tree N nutrition with N from SOM across the ecosystems in our study (Pellitier, Ibáñez, et al, 2021;, and our current findings suggest this enhanced decay, in turn, reduces lignin-derived SOM and soil C storage (Figure 6). We propose that this nutritional tradeoff continues to operate in relatively fertile boreal forests, in which ECM fungi with peroxidases decline with increasing N availability and plausibly enable greater SOM decay by ligninolytic saprotrophs (Figure 6; Kyaschenko et al, 2017).…”
Section: Discussion Turnover In Ecm Composition Constrains Som Accumu...mentioning
confidence: 90%
See 3 more Smart Citations
“…Specifically, investment in ECM symbionts with energetically costly organic N acquisition capacities is beneficial to plant hosts where inorganic N is scarce, favouring ECM taxa with a greater genetic potential to obtain N from SOM using peroxidases and other oxidative enzymes (Baskaran et al, 2017;Defrenne et al, 2019;. These decay traits enable ECM communities in soils with low inorganic N availability to more substantially supplement tree N nutrition with N from SOM across the ecosystems in our study (Pellitier, Ibáñez, et al, 2021;, and our current findings suggest this enhanced decay, in turn, reduces lignin-derived SOM and soil C storage (Figure 6). We propose that this nutritional tradeoff continues to operate in relatively fertile boreal forests, in which ECM fungi with peroxidases decline with increasing N availability and plausibly enable greater SOM decay by ligninolytic saprotrophs (Figure 6; Kyaschenko et al, 2017).…”
Section: Discussion Turnover In Ecm Composition Constrains Som Accumu...mentioning
confidence: 90%
“…Our plots ranged in mineralisation rates from 0.08 to 1.19 μg N g −1 day −1 (Figure ). These values captured the full gradient of inorganic N availability in the upper Lake States region and have remained seasonally and interannually stable since the 1980s (Pellitier, Ibáñez, et al, 2021; Zak et al, 1989; Zak & Pregitzer, 1990).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The entire period covered was 1999–2017, the mean initial census year was 2005, the mean final census year was 2008, and the mean growth interval was 5.5 years. Although there is some variation in the annual sampling of tree growth versus the fungal community at some sites, previous work has shown that year-to-year variation in fungal communities is low at regional to continental scales [ 42 , 43 ]. Allometric equations for dominant tree species within our observed size and geographic range were used to calculate aboveground biomass using equations from the GlobeAllomeTree database [ 44 ]:…”
Section: Methodsmentioning
confidence: 99%